PENGARUH GOOD CORPORATE GOVERNANCE, PROFITABILITAS, UKURAN PERUSAHAAN, dan INTENSITAS ASET TETAP TERHADAP AGRESIVITAS PAJAK (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Junita Indriyati; Marjono Marjono; Lia Nurina (STIE 'INDONESIA' Pontianak, 2022)
This research aims to obtain empirical evidence about the influence of good corporate governance, profitability, company size, and capital intensity on tax aggressiveness on manufacturing companies listed on the Indonesia Stock Exchange 2015-2019). The sampling method used purposive sampling and obtained 31 companies based on certain criteria and this study used multiple linear regression analysis to analyze data with SPSS 25. The sample of the study was determined using purposive sampling, then multiple analysis was performed using SPSS 25. The results of this study indicate that: (1) the boards of independent commissioners have not to affect on tax aggressiveness, (2) the audit committee affects tax aggressiveness, (3) profitability affects tax aggressiveness, (4) company size has no effect on tax aggressiveness, (5) capital intensity has an effect on tax aggressiveness, (6) boards of the independent commissioner, audit committee, profitability, company size, and capital intensity simultaneously have an effect on tax aggressiveness.